Prevalence of cardiac comorbidities, and their underdetection and contribution to exertional symptoms in COPD: results from the COSYCONET cohort - Alter P; Mayerhofer BA; Kahnert K; Watz H; Waschki B; Andreas S; Biertz F; Bals R; Vogelmeier CF; Jörres RA (International Journal of COPD, 2019)
Peter Alter,1 Barbara A Mayerhofer,2 Kathrin Kahnert,3 Henrik Watz,4 Benjamin Waschki,5,6 Stefan Andreas,7,8 Frank Biertz,9 Robert Bals,10 Claus F Vogelmeier,1 Rudolf A Jörres2 1Department of Medicine, Pulmonary and Critical Care Medicine, Philipps University of Marburg (UMR), Member of the German Center for Lung Research (DZL), Marburg, Germany; 2Institute and Outpatient Clinic for Occupational, Social and Environmental Medicine, University Hospital, LMU Munich, Comprehensive Pneumology Center Munich (CPC-M), Member of the Center for Lung Research (DZL), Munich, Germany; 3Department of Internal Medicine V, University Hospital, LMU Munich, Comprehensive Pneumology Center Munich (CPC-M), Member of the German Center for Lung Research (DZL), Munich, Germany; 4Pulmonary Research Institute at Lungen Clinic Grosshansdorf, Airway Research Center North (ARCN), Member of the German Center for Lung Research (DZL), Grosshansdorf, Germany; 5Department of Pneumology, LungenClinic Grosshansdorf, Airway Research Center North (ARCN), Member of the German Center for Lung Research (DZL), Grosshansdorf, Germany; 6Department of General and Interventional Cardiology, University Heart Center, Hamburg, Germany; 7Department of Cardiology and Pneumology, University Medical Center, Goettingen, Germany; 8Lung Clinic, Immenhausen, Germany; 9Institute for Biostatistics, Center for Biometry, Medical Informatics and Medical Technology, Hannover Medical School, Hannover, Germany; 10Department of Internal Medicine V - Pulmonology, Allergology, Intensive Care Medicine, Saarland University Hospital, Homburg, GermanyCorrespondence: Peter AlterDepartment of Medicine, Pulmonary and Critical Care Medicine, Philipps University of Marburg (UMR), Member of the German Center for Lung Research (DZL), Baldingerstrasse 1, Marburg 35033, GermanyTel +49 6 421 586 6140Email Alter@uni-marburg.de&#x00A0Rudolf A JörresInstitute and Outpatient Clinic for Occupational, Social and Environmental Medicine, University Hospital, LMU Munich, Comprehensive Pneumology Center Munich (CPC-M), Member of the Center for Lung Research (DZL), Ziemssenstrasse 1, Munich 80336, GermanyTel +49 8 944 005 2466Email Rudolf.Joerres@med.uni-muenchen.de &#x00A0Background: A substantial prevalence of cardiovascular disease is known for COPD, but detection of its presence, relationship to functional findings and contribution to symptoms remains challenging. The present analysis focusses on the cardiovascular contribution to COPD symptoms and their relationship to the patients’ diagnostic status, medication and echocardiographic findings.Methods: Patients from the COPD cohort COSYCONET with data on lung function, including FEV1, residual volume/total lung capacity (RV/TLC) ratio, diffusing capacity TLCO, and echocardiographic data on left ventricular ejection fraction (LVEF) and end-diastolic diameter (LVEDD), medical history, medication, modified British Medical Research Council dyspnea scale (mMRC) and Saint Georges Respiratory Questionnaire (SGRQ) were analyzed.Results: A total of 1591 patients (GOLD 0–4: n=230/126/614/498/123) fulfilled the inclusion criteria. Ischemic heart disease, myocardial infarction or heart failure were reported in 289 patients (18.2%); 860 patients (54%) received at least one cardiovascular medication, with more than one in many patients. LVEF<50% or LVEDD>56 mm was found in 204 patients (12.8%), of whom 74 (36.3%) had neither a cardiovascular history nor medication. Among 948 patients (59.6%) without isolated hypertension, there were 21/55 (38.2%) patients with LVEF<50% and 47/88 (53.4%) with LVEDD>56 mm, who lacked both a cardiac diagnosis and medication. LVEDD and LVEF were linked to medical history; LVEDD was dependent on RV/TLC and LVEF on FEV1. Exertional COPD symptoms were best described by mMRC and the SGRQ activity score. Beyond lung function, an independent link from LVEDD on symptoms was revealed.Conclusion: A remarkable proportion of patients with suspicious echocardiographic findings were undiagnosed and untreated, implying an increased risk for an unfavorable prognosis. Cardiac size and function were dependent on lung function and only partially linked to cardiovascular history. Although the contribution of LV size to COPD symptoms was small compared to lung function, it was detectable irrespective of all other influencing factors. However, only the mMRC and SGRQ activity component were found to be suitable for this purpose.Keywords: COPD, heart failure, echocardiography, medication, dyspnea, symptoms